A processing technology of ceramic copper clad plate
The copper plate is prepared by modifying carbon nanotubes and copper powder, and combined with the aluminum nitride ceramic substrate, which solves the thermal stress problem caused by the different thermal expansion coefficients of the ceramic substrate and the copper layer, improves the reliability and stability of the ceramic copper-clad laminate, and prolongs service life.
Patent Information
- Application Number
- CN202410559008.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-08
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-05-08
AI Technical Summary
The thermal stress problems at the bonding interface caused by different thermal expansion coefficients of the ceramic substrate and the copper layer, and the inseparable bonding between the ceramic substrate and the copper layer, affect the stability, reliability and service life of the power module.
A copper plate is prepared by using modified carbon nanotubes and copper powder, and is combined with an aluminum nitride ceramic substrate through active metal brazing to form a ceramic copper-clad plate. Modified carbon nanotubes reduce the linear expansion coefficient of copper materials through surface modification and metal plating, improve thermal and electrical conductivity, and enhance the bonding strength of ceramics and copper sheets.
It improves the reliability and stability of ceramic copper-clad laminates, reduces thermal stress during welding, extends service life, and improves the yield rate of copper-clad laminates.
Smart Images

Figure BDA0004826966000000101
Abstract
Description
Technical Field
[0001] The invention relates to the field of ceramic copper-clad laminates, and specifically discloses a processing technology for ceramic copper-clad laminates. Background Art
[0002] Ceramic-based packaging substrates have excellent performance, good dimensional stability, low thermal conductivity, low dielectric constant and dielectric loss, etc., so they are widely used. When ceramics are used as packaging substrate materials, their surfaces need to be copper-clad. The type of ceramic substrate and the stability of the combination of the substrate and the copper layer are closely related to the stability of power electronic devices during operation, and have been a hot topic of research in recent years.
[0003] Aluminum nitride has great advantages, such as high thermal conductivity, thermal expansion coefficient similar to that of metal layer, good electrical insulation and excellent mechanical properties; however, the thermal stress problem at the bonding interface caused by the different thermal expansion coefficients of the ceramic substrate and the copper layer still exists, and the insufficient bonding between the ceramic substrate and the copper layer will also affect the stability, reliability and service life of the entire power module. Therefore, it is of great significance to study a ceramic copper clad laminate with high reliability, high stability, durability and excellent performance. Summary of the invention
[0004] The object of the present invention is to provide a processing technology for a ceramic copper clad laminate to solve the problems raised in the above background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a processing technology of a ceramic copper clad laminate, comprising the following steps:
[0006] S1: Take carbon nanotubes, modify the surface to obtain carbon nanotube A; plate chromium and nickel to obtain carbon nanotube B; plate molybdenum and tungsten to obtain carbon nanotube C; plate cuprous oxide to obtain modified carbon nanotubes;
[0007] S2: mixing the modified carbon nanotubes with copper powder, sintering to obtain a blank; extruding, hot rolling, and cold rolling the blank in sequence to obtain a copper plate;
[0008] S3: pre-treating the copper plate to obtain a pre-treated copper sheet; performing active metal brazing on the pre-treated copper sheet and the aluminum nitride ceramic substrate, and vacuum sintering to obtain a ceramic copper-clad laminate.
[0009] Preferably, the copper powder is prepared by gas atomization powder making technology, the powder making temperature is 1200° C., the holding time is 30 min, the atomizing gas flow rate is 30 m / min, and the atomizing gas pressure is 5.0 MPa.
[0010] Preferably, an active metal brazing material Ag-Cu-Ti is used, which contains 25.5% Cu, 5.0% Ti and the balance Ag.
[0011] Preferably, the added amounts of the modified carbon nanotubes and copper powder are as follows: 6-10% of the modified carbon nanotubes and the remainder of the copper powder by mass percentage.
[0012] Preferably, the preparation of the carbon nanotubes A specifically includes the following steps: taking carbon nanotubes, DMF, and trimethylolpropane triglycidyl ether, heating to 130-140° C. and stirring for 4-6 hours, adding di(2-hydroxyethyl)iminotri(hydroxymethyl)methane and 2,4,6-triaminopyrimidine, maintaining 130-140° C. and stirring for 6-8 hours, filtering, drying, and washing to obtain carbon nanotubes A.
[0013] Preferably, the carbon nanotube A comprises the following raw materials, by mass: 15 to 20 parts of carbon nanotubes, 150 to 200 parts of DMF, 4 to 8 parts of trimethylolpropane triglycidyl ether, 6 to 10 parts of di(2-hydroxyethyl)iminotri(hydroxymethyl)methane, and 10 to 15 parts of 2,4,6-triaminopyrimidine; the carbon nanotube is a hydroxylated single-arm carbon nanotube.
[0014] Preferably, the preparation of the carbon nanotubes B specifically includes the following steps: pre-treating the carbon nanotubes A, plating chromium and nickel on the surface by chemical plating, washing, and drying to obtain the carbon nanotubes B; the chemical plating process is specifically: placing the pre-treated carbon nanotubes A in a chemical plating solution A with a pH value of 11 to 12 for 50 to 60 minutes at a temperature of 75 to 80°C; the raw materials of the chemical plating solution A are measured in terms of concentration: 6 to 10 g / L of chromium sulfate, 6 to 10 g / L of nickel sulfate, 20 to 25 g / L of disodium ethylenediaminetetraacetate, 10 to 15 g / L of potassium sodium tartrate, and 15 to 20 ml / L of hydrazine hydrate.
[0015] Preferably, the pretreatment specifically includes the following steps: sensitization for 25 to 30 minutes, activation for 10 to 12 minutes; the raw materials of the sensitizing solution are calculated by concentration: 15 to 20 g / L stannous chloride, 60 to 70 ml / L hydrochloric acid, and the rest is water; the raw materials of the activation solution are calculated by concentration: 0.05 to 0.08 g / L palladium chloride, 8 to 9 ml / L hydrochloric acid, and the rest is water.
[0016] Preferably, the pretreatment specifically includes the following steps: sensitization for 30 minutes and activation for 10 minutes; the raw materials of the sensitizing solution are calculated by concentration: 20g / L stannous chloride, 60ml / L hydrochloric acid, and the rest is water; the raw materials of the activation solution are calculated by concentration: 0.05g / L palladium chloride, 8ml / L hydrochloric acid, and the rest is water.
[0017] Preferably, the preparation of the carbon nanotubes C specifically includes the following steps: taking carbon nanotubes B, coating the surface with molybdenum and tungsten by chemical plating, washing, and drying to obtain carbon nanotubes C; the chemical plating process specifically includes: placing the carbon nanotubes B in a chemical plating solution B with a pH value of 11 to 12 for 50 to 60 minutes at a temperature of 75 to 80°C; the raw materials of the chemical plating solution B are measured in terms of concentration: 15 to 20 g / L of sodium tungstate, 6 to 10 g / L of molybdenum sulfate, 20 to 25 g / L of disodium ethylenediaminetetraacetate, 10 to 15 g / L of potassium sodium tartrate, and 15 to 20 ml / L of hydrazine hydrate.
[0018] Preferably, the preparation of the modified carbon nanotubes specifically includes the following steps: taking carbon nanotubes C, coating the surface with cuprous oxide by chemical plating, washing, and drying to obtain modified carbon nanotubes; the chemical plating process is specifically: placing the carbon nanotubes C in a chemical plating solution C for 50 to 60 minutes at a temperature of 75 to 80°C; the preparation of the chemical plating solution C includes the following steps: taking 15 to 20 parts of copper sulfate pentahydrate, 45 to 50 parts of lactic acid, 5 to 8 parts of disodium ethylenediaminetetraacetate, and 1 to 2 parts of formaldehyde, stirring evenly, adding water to dilute to 1L, and adding sodium hydroxide to adjust the pH to 11 to 12 to obtain a chemical plating solution C.
[0019] Preferably, the copper plate pretreatment step is: ultrasonically clean the copper plate in acetone, blow dry, place it in a chain furnace, introduce nitrogen as a protective gas, and introduce oxygen, and treat it at 750-800°C for 20-25min; wherein the oxygen concentration in the chain furnace is 300ppm; pickling with a 5wt% sulfuric acid aqueous solution for 8-10s, washing with water, and drying to obtain a pretreated copper sheet.
[0020] Preferably, the copper plate pretreatment step is: placing the copper plate in acetone for ultrasonic cleaning for 60 minutes, blowing dry, placing it in a chain furnace, introducing nitrogen as a protective gas, and introducing oxygen, and treating it at 800°C for 20 minutes; wherein the oxygen concentration in the chain furnace is 300ppm; using a 5wt% sulfuric acid aqueous solution for pickling for 8s, washing with water, and drying to obtain a pretreated copper sheet.
[0021] Preferably, the vacuum sintering process is: keeping the temperature at 850-950° C. for 0.5-1 h.
[0022] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: a copper plate is prepared by using modified carbon nanotubes and copper powder, and after pretreatment, the copper plate is compounded with an aluminum nitride ceramic substrate to obtain a ceramic copper-clad laminate; the modified carbon nanotubes are obtained by surface modification of hydroxylated single-arm carbon nanotubes, plating with chromium and nickel, plating with molybdenum and tungsten, and plating with cuprous oxide; the addition of the single-arm carbon nanotubes can reduce the linear expansion coefficient of the copper material, while ensuring the thermal and electrical conductivity, reducing the reliability reduction caused by the inconsistency of the linear expansion coefficients of the copper material and the ceramic substrate during welding, thereby improving the yield rate and service life of the copper-clad laminate;
[0023] The specific steps of surface modification are: firstly modify the carbon nanotubes with hydroxyl groups with trimethylolpropane triglycidyl ether to make them have epoxy groups, and at the same time, the ether bond has good wettability, can reduce the interfacial tension, and improve the uniformity and stability of the subsequent plated metal layer; then add di(2-hydroxyethyl)iminotri(hydroxymethyl)methane and 2,4,6-triaminopyrimidine, di(2-hydroxyethyl)iminotri(hydroxymethyl)methane contains multiple hydroxyl groups, and the smoothness and stability of the coating are improved through hydrogen bonds and van der Waals forces, while 2,4,6-triaminopyrimidine is a nitrogen-containing heterocyclic compound, and its molecular planarity helps the coating to be adsorbed on the surface of the carbon nanotube in an orderly manner to obtain a flat coating, wherein the multiple amino groups play a complexing role, and play a synergistic role with di(2-hydroxyethyl)iminotri(hydroxymethyl)methane to assist the coating; in summary, surface modification before coating helps to improve the flatness and stability of the coating, helps to improve the quality of the coating, and improves the reliability and stability of the copper clad laminate;
[0024] After the surface modification is completed, chromium and nickel are plated first. Chromium can inhibit the abnormal growth of grains and improve the sintering yield; nickel as the bottom layer can improve the adhesion and uniformity of the next layer of molybdenum and tungsten.
[0025] The thermal expansion coefficients of molybdenum and tungsten are similar to those of the aluminum nitride ceramic substrate, which can reduce the internal stress between the copper layer and the ceramic substrate, and can improve the conductivity and corrosion resistance of the carbon nanotube material. At the same time, molybdenum and tungsten have good anti-migration ability and can block the migration of chromium and nickel. If chromium and nickel migrate, they will affect the conductivity and electrochemical properties of the copper layer. In addition, due to the strong corrosion resistance of chromium, the subsequent etching steps of the copper layer will cause complex processes and increased costs. Therefore, chromium and nickel should be coated in the innermost layer of the plating layer;
[0026] Cuprous oxide is plated on the outside of molybdenum and tungsten. Cuprous oxide can react with Al in the aluminum nitride ceramic substrate to generate spinel substances of CuAlO2 and CuAl2O4, thereby improving the bonding strength between the ceramic and the copper sheet. In the process of directly oxidizing the copper sheet and then compounding it with the ceramic substrate, it is often difficult to obtain enough cuprous oxide during the oxidation process, and the formed oxide layer is often a mixture of CuO and cuprous oxide. If there is too much CuO, CuO will release oxygen at high temperature to form tiny pores, which will affect the bonding strength. DETAILED DESCRIPTION
[0027] The following is a preferred implementation of the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. For ordinary technicians in this technical field, all other embodiments obtained by ordinary technicians in this field without creative work without departing from the principle of the embodiment of the present invention are within the scope of protection of the present invention.
[0028] The following parts are by mass unless otherwise specified;
[0029] Example 1: S1: Take 20 parts of carbon nanotubes, 200 parts of DMF, and 6 parts of trimethylolpropane triglycidyl ether, heat to 140°C and stir for 4 hours, add 8 parts of di(2-hydroxyethyl)iminotri(hydroxymethyl)methane and 12 parts of 2,4,6-triaminopyrimidine, keep stirring at 140°C for 7 hours, filter, dry, and wash to obtain carbon nanotubes A;
[0030] S2: pre-treating carbon nanotubes A, placing the pre-treated carbon nanotubes A in a chemical plating solution A with a pH value of 12 for 60 minutes at a temperature of 80° C., washing, and drying to obtain carbon nanotubes B;
[0031] Chemical plating solution A: in terms of concentration, chromium sulfate 10g / L, nickel sulfate 6g / L, disodium ethylenediaminetetraacetate 25g / L, potassium sodium tartrate 15g / L, hydrazine hydrate 18ml / L;
[0032] S3: placing carbon nanotubes B in a chemical plating solution B with a pH value of 12 for 60 minutes at a temperature of 80°C; washing and drying to obtain carbon nanotubes C;
[0033] Chemical plating solution B: in terms of concentration, sodium tungstate 18g / L, molybdenum sulfate 8g / L, disodium ethylenediaminetetraacetate 25g / L, potassium sodium tartrate 15g / L, hydrazine hydrate 18ml / L;
[0034] S4: taking carbon nanotubes C, placing them in a chemical plating solution C with a pH value of 12 for 60 minutes at a temperature of 80°C; washing and drying to obtain modified carbon nanotubes;
[0035] The preparation of chemical plating solution C comprises the following steps: taking 20 parts of copper sulfate pentahydrate, 50 parts of lactic acid, 5 parts of disodium ethylenediaminetetraacetate, and 1-2 parts of formaldehyde, stirring evenly, adding water to dilute to 1L, adding sodium hydroxide to adjust the pH to 12, and obtaining chemical plating solution C;
[0036] S5: mixing the modified carbon nanotubes and copper powder, and placing them in a sintering furnace for sintering to obtain a blank; the amount of the modified carbon nanotubes and copper powder added is as follows: 8% of the modified carbon nanotubes and the rest of the copper powder;
[0037] The blank is sequentially extruded, hot rolled and cold rolled to obtain a copper plate with a thickness of 0.3 mm; the copper plate is pretreated to obtain a pretreated copper sheet; the pretreated copper sheet is brazed with a 1 mm aluminum nitride ceramic substrate by active metal brazing, and then placed in a vacuum furnace for sintering at a sintering temperature of 870°C for 1 hour to obtain a ceramic copper clad laminate.
[0038] Example 2: S1: Take 20 parts of carbon nanotubes, 200 parts of DMF, and 8 parts of trimethylolpropane triglycidyl ether, heat to 140°C and stir for 4 hours, add 10 parts of di(2-hydroxyethyl)iminotri(hydroxymethyl)methane and 15 parts of 2,4,6-triaminopyrimidine, keep stirring at 140°C for 7 hours, filter, dry, and wash to obtain carbon nanotubes A;
[0039] S2: pre-treating carbon nanotubes A, placing the pre-treated carbon nanotubes A in a chemical plating solution A with a pH value of 12 for 60 minutes at a temperature of 80° C., washing, and drying to obtain carbon nanotubes B;
[0040] Chemical plating solution A: in terms of concentration, chromium sulfate 10g / L, nickel sulfate 10g / L, disodium ethylenediaminetetraacetate 25g / L, potassium sodium tartrate 15g / L, hydrazine hydrate 20ml / L;
[0041] S3: placing carbon nanotubes B in a chemical plating solution B with a pH value of 12 for 60 minutes at a temperature of 80°C; washing and drying to obtain carbon nanotubes C;
[0042] Chemical plating solution B: in terms of concentration, sodium tungstate 20g / L, molybdenum sulfate 10g / L, disodium ethylenediaminetetraacetic acid 25g / L, potassium sodium tartrate 15g / L, hydrazine hydrate 20ml / L;
[0043] S4: taking carbon nanotubes C, placing them in a chemical plating solution C with a pH value of 12 for 60 minutes at a temperature of 80°C; washing and drying to obtain modified carbon nanotubes;
[0044] The preparation of chemical plating solution C includes the following steps: taking 20 parts of copper sulfate pentahydrate, 50 parts of lactic acid, 8 parts of disodium ethylenediaminetetraacetate, and 2 parts of formaldehyde, stirring evenly, adding water to dilute to 1L, adding sodium hydroxide to adjust the pH to 12, and obtaining chemical plating solution C;
[0045] S5: mixing the modified carbon nanotubes and copper powder, and placing them in a sintering furnace for sintering to obtain a blank; the amount of the modified carbon nanotubes and copper powder added is as follows: 10% of the modified carbon nanotubes and the rest of the copper powder;
[0046] The blank is sequentially extruded, hot rolled and cold rolled to obtain a copper plate with a thickness of 0.3 mm; the copper plate is pretreated to obtain a pretreated copper sheet; the pretreated copper sheet is brazed with a 1 mm aluminum nitride ceramic substrate by active metal brazing, and then placed in a vacuum furnace for sintering at a sintering temperature of 870°C for 1 hour to obtain a ceramic copper clad laminate.
[0047] Example 3: S1: Take 15 parts of carbon nanotubes, 150 parts of DMF, and 4-8 parts of trimethylolpropane triglycidyl ether, heat to 140°C and stir for 4 hours, add 6 parts of di(2-hydroxyethyl)iminotri(hydroxymethyl)methane and 10 parts of 2,4,6-triaminopyrimidine, keep stirring at 140°C for 7 hours, filter, dry, and wash to obtain carbon nanotubes A;
[0048] S2: pre-treating carbon nanotubes A, placing the pre-treated carbon nanotubes A in a chemical plating solution A with a pH value of 12 for 60 minutes at a temperature of 80° C., washing, and drying to obtain carbon nanotubes B;
[0049] Chemical plating solution A: in terms of concentration, chromium sulfate 6g / L, nickel sulfate 6g / L, disodium ethylenediaminetetraacetate 20g / L, potassium sodium tartrate 10g / L, hydrazine hydrate 15ml / L;
[0050] S3: placing carbon nanotubes B in a chemical plating solution B with a pH value of 12 for 60 minutes at a temperature of 80°C; washing and drying to obtain carbon nanotubes C;
[0051] Chemical plating solution B: in terms of concentration, sodium tungstate 20g / L, molybdenum sulfate 10g / L, disodium ethylenediaminetetraacetate 20g / L, potassium sodium tartrate 10g / L, hydrazine hydrate 15ml / L;
[0052] S4: taking carbon nanotubes C, placing them in a chemical plating solution C with a pH value of 12 for 60 minutes at a temperature of 80°C; washing and drying to obtain modified carbon nanotubes;
[0053] The preparation of chemical plating solution C comprises the following steps: taking 15 parts of copper sulfate pentahydrate, 45 parts of lactic acid, 5 parts of disodium ethylenediaminetetraacetate, and 1 part of formaldehyde, stirring evenly, adding water to dilute to 1L, adding sodium hydroxide to adjust the pH to 12, and obtaining chemical plating solution C;
[0054] S5: mixing the modified carbon nanotubes and copper powder, and placing them in a sintering furnace for sintering to obtain a blank; the added amounts of the modified carbon nanotubes and copper powder are as follows: 6% of the modified carbon nanotubes and the remainder of the copper powder;
[0055] The blank is sequentially extruded, hot rolled and cold rolled to obtain a copper plate with a thickness of 0.3 mm; the copper plate is pretreated to obtain a pretreated copper sheet; the pretreated copper sheet is brazed with a 1 mm aluminum nitride ceramic substrate by active metal brazing, and then placed in a vacuum furnace for sintering at a sintering temperature of 870°C for 1 hour to obtain a ceramic copper clad laminate.
[0056] Comparative Example 1 (replacing carbon nanotubes A with carbon nanotubes, and the remaining steps are consistent with those of Example 1): S1: pre-treating the carbon nanotubes, placing the pre-treated carbon nanotubes A in a chemical plating solution A with a pH value of 12 for 60 minutes at a temperature of 80° C., washing, and drying to obtain carbon nanotubes B;
[0057] Chemical plating solution A: in terms of concentration, chromium sulfate 10g / L, nickel sulfate 6g / L, disodium ethylenediaminetetraacetate 25g / L, potassium sodium tartrate 15g / L, hydrazine hydrate 18ml / L;
[0058] S2: placing carbon nanotubes B in a chemical plating solution B with a pH value of 12 for 60 minutes at a temperature of 80°C; washing and drying to obtain carbon nanotubes C;
[0059] Chemical plating solution B: in terms of concentration, sodium tungstate 18g / L, molybdenum sulfate 8g / L, disodium ethylenediaminetetraacetate 25g / L, potassium sodium tartrate 15g / L, hydrazine hydrate 18ml / L;
[0060] S3: taking carbon nanotubes C, placing them in a chemical plating solution C with a pH value of 12 for 60 minutes at a temperature of 80°C; washing and drying to obtain modified carbon nanotubes;
[0061] The preparation of chemical plating solution C comprises the following steps: taking 20 parts of copper sulfate pentahydrate, 50 parts of lactic acid, 5 parts of disodium ethylenediaminetetraacetate, and 1-2 parts of formaldehyde, stirring evenly, adding water to dilute to 1L, adding sodium hydroxide to adjust the pH to 12, and obtaining chemical plating solution C;
[0062] S4: mixing the modified carbon nanotubes and copper powder, and placing them in a sintering furnace for sintering to obtain a blank; the added amounts of the modified carbon nanotubes and copper powder are as follows: 8% of the modified carbon nanotubes and the remainder of the copper powder;
[0063] The blank is sequentially extruded, hot rolled and cold rolled to obtain a copper plate with a thickness of 0.3 mm; the copper plate is pretreated to obtain a pretreated copper sheet; the pretreated copper sheet is brazed with a 1 mm aluminum nitride ceramic substrate by active metal brazing, and then placed in a vacuum furnace for sintering at a sintering temperature of 870°C for 1 hour to obtain a ceramic copper clad laminate.
[0064] Comparative Example 2 (increasing the amount of modified carbon nanotubes added, and the remaining method steps are consistent with Example 1): S1: Take 20 parts of carbon nanotubes, 200 parts of DMF, and 6 parts of trimethylolpropane triglycidyl ether, heat to 140° C. and stir for 4 hours, add 8 parts of di(2-hydroxyethyl)iminotri(hydroxymethyl)methane and 12 parts of 2,4,6-triaminopyrimidine, keep stirring at 140° C. for 7 hours, filter, dry, and wash to obtain carbon nanotubes A;
[0065] S2: pre-treating carbon nanotubes A, placing the pre-treated carbon nanotubes A in a chemical plating solution A with a pH value of 12 for 60 minutes at a temperature of 80° C., washing, and drying to obtain carbon nanotubes B;
[0066] Chemical plating solution A: in terms of concentration, chromium sulfate 10g / L, nickel sulfate 6g / L, disodium ethylenediaminetetraacetate 25g / L, potassium sodium tartrate 15g / L, hydrazine hydrate 18ml / L;
[0067] S3: placing carbon nanotubes B in a chemical plating solution B with a pH value of 12 for 60 minutes at a temperature of 80°C; washing and drying to obtain carbon nanotubes C;
[0068] Chemical plating solution B: in terms of concentration, sodium tungstate 18g / L, molybdenum sulfate 8g / L, disodium ethylenediaminetetraacetate 25g / L, potassium sodium tartrate 15g / L, hydrazine hydrate 18ml / L;
[0069] S4: taking carbon nanotubes C, placing them in a chemical plating solution C with a pH value of 12 for 60 minutes at a temperature of 80°C; washing and drying to obtain modified carbon nanotubes;
[0070] The preparation of chemical plating solution C comprises the following steps: taking 20 parts of copper sulfate pentahydrate, 50 parts of lactic acid, 5 parts of disodium ethylenediaminetetraacetate, and 1-2 parts of formaldehyde, stirring evenly, adding water to dilute to 1L, adding sodium hydroxide to adjust the pH to 12, and obtaining chemical plating solution C;
[0071] S5: mixing the modified carbon nanotubes and copper powder, and placing them in a sintering furnace for sintering to obtain a blank; the amount of the modified carbon nanotubes and copper powder added is as follows: 15% of the modified carbon nanotubes and the rest of the copper powder;
[0072] The blank is sequentially extruded, hot rolled and cold rolled to obtain a copper plate with a thickness of 0.3 mm; the copper plate is pretreated to obtain a pretreated copper sheet; the pretreated copper sheet is brazed with a 1 mm aluminum nitride ceramic substrate by active metal brazing, and then placed in a vacuum furnace for sintering at a sintering temperature of 870°C for 1 hour to obtain a ceramic copper clad laminate.
[0073] Comparative Example 3 (replacing the modified carbon nanotubes with carbon nanotubes C, and the remaining steps are consistent with those of Example 1): S1: Take 20 parts of carbon nanotubes, 200 parts of DMF, and 6 parts of trimethylolpropane triglycidyl ether, heat to 140° C. and stir for 4 h, add 8 parts of di(2-hydroxyethyl)iminotri(hydroxymethyl)methane and 12 parts of 2,4,6-triaminopyrimidine, keep stirring at 140° C. for 7 h, filter, dry, and wash to obtain carbon nanotubes A;
[0074] S2: pre-treating carbon nanotubes A, placing the pre-treated carbon nanotubes A in a chemical plating solution A with a pH value of 12 for 60 minutes at a temperature of 80° C., washing, and drying to obtain carbon nanotubes B;
[0075] Chemical plating solution A: in terms of concentration, chromium sulfate 10g / L, nickel sulfate 6g / L, disodium ethylenediaminetetraacetate 25g / L, potassium sodium tartrate 15g / L, hydrazine hydrate 18ml / L;
[0076] S3: placing carbon nanotubes B in a chemical plating solution B with a pH value of 12 for 60 minutes at a temperature of 80°C; washing and drying to obtain carbon nanotubes C;
[0077] Chemical plating solution B: in terms of concentration, sodium tungstate 18g / L, molybdenum sulfate 8g / L, disodium ethylenediaminetetraacetate 25g / L, potassium sodium tartrate 15g / L, hydrazine hydrate 18ml / L;
[0078] S4: mixing carbon nanotubes C and copper powder, placing them in a sintering furnace for sintering, and obtaining a blank; the amount of the modified carbon nanotubes and copper powder added is as follows: 8% carbon nanotubes C, and the remainder is copper powder;
[0079] The blank is sequentially extruded, hot rolled and cold rolled to obtain a copper plate with a thickness of 0.3 mm; the copper plate is pretreated to obtain a pretreated copper sheet; the pretreated copper sheet is brazed with a 1 mm aluminum nitride ceramic substrate by active metal brazing, and then placed in a vacuum furnace for sintering at a sintering temperature of 870°C for 1 hour to obtain a ceramic copper clad laminate.
[0080] Comparative Example 4 (no chromium and nickel plating, the remaining method steps are consistent with Example 1): S1: Take 20 parts of carbon nanotubes, 200 parts of DMF, and 6 parts of trimethylolpropane triglycidyl ether, heat to 140° C. and stir for 4 hours, add 8 parts of di(2-hydroxyethyl)iminotri(hydroxymethyl)methane and 12 parts of 2,4,6-triaminopyrimidine, keep stirring at 140° C. for 7 hours, filter, dry, and wash to obtain carbon nanotubes A;
[0081] S2: pre-treating the carbon nanotubes A, placing the pre-treated carbon nanotubes A in a chemical plating solution B with a pH value of 12 for 60 minutes at a temperature of 80° C., washing, and drying to obtain carbon nanotubes C;
[0082] Chemical plating solution B: in terms of concentration, sodium tungstate 18g / L, molybdenum sulfate 8g / L, disodium ethylenediaminetetraacetate 25g / L, potassium sodium tartrate 15g / L, hydrazine hydrate 18ml / L;
[0083] S3: taking carbon nanotubes C, placing them in a chemical plating solution C with a pH value of 12 for 60 minutes at a temperature of 80°C; washing and drying to obtain modified carbon nanotubes;
[0084] The preparation of chemical plating solution C comprises the following steps: taking 20 parts of copper sulfate pentahydrate, 50 parts of lactic acid, 5 parts of disodium ethylenediaminetetraacetate, and 1-2 parts of formaldehyde, stirring evenly, adding water to dilute to 1L, adding sodium hydroxide to adjust the pH to 12, and obtaining chemical plating solution C;
[0085] S4: mixing the modified carbon nanotubes and copper powder, and placing them in a sintering furnace for sintering to obtain a blank; the added amounts of the modified carbon nanotubes and copper powder are as follows: 8% of the modified carbon nanotubes and the remainder of the copper powder;
[0086] The blank is sequentially extruded, hot rolled and cold rolled to obtain a copper plate with a thickness of 0.3 mm; the copper plate is pretreated to obtain a pretreated copper sheet; the pretreated copper sheet is brazed with a 1 mm aluminum nitride ceramic substrate by active metal brazing, and then placed in a vacuum furnace for sintering at a sintering temperature of 870°C for 1 hour to obtain a ceramic copper clad laminate.
[0087] In the above embodiments, the test methods used are conventional methods unless otherwise specified; the raw materials used are commercially available unless otherwise specified, and the sources of the raw materials are as follows: carbon nanotubes (CF2023122, Hubei Chengfeng Chemical Co., Ltd.); DMF (CAS: 68-12-2); trimethylolpropane triglycidyl ether (CAS: 30499-70-8, item number: S64328, Shanghai Yuanye); bis(2-hydroxyethyl)iminotri(hydroxymethyl)methane (CAS: 6976-37-0, item number: PA07636, Shanghai Yimiao Chemical Technology Co., Ltd.); 2,4,6-triaminopyrimidine (CAS: 1004-38-2); stannous chloride (S24125, Shanghai =Haiyuanye); palladium chloride (V900829, VETEC); chromium sulfate (Cat. No.: 145916, Kramar); nickel sulfate (Cat. No.: 656895, ALDRICH); disodium ethylenediaminetetraacetic acid (CAS: 139-33-3); potassium sodium tartrate (S30441, Shanghai Yuanye); hydrazine hydrate (CAS: 7803-57-8); sodium tungstate (S61169, Shanghai Yuanye); molybdenum sulfate (BD2386, Hubei Baidu Chemical Co., Ltd.); copper sulfate pentahydrate (S24261, Shanghai Yuanye); lactic acid (W261114, ALDRICH); formaldehyde (CAS: 50-00-0); aluminum nitride ceramic substrate (AN-170, MARUWA).
[0088] Experiment: Take the ceramic copper-clad laminates prepared in Examples 1 to 3 and Comparative Examples 1 to 4, (1) test the number of high and low temperature cycles: after keeping at -50°C for 15 minutes, heat it to 150°C for 15 minutes, and then cool it to -50°C, which is one cycle; record the number of cycles until the ceramic copper-clad laminate cracks or the copper layer peels off; (2) test the peel strength on a universal tensile testing machine, and make a peeling strip pattern by etching before the peel strength test, and measure the peel strength at 90° vertically; see the table below for specific data;
[0089]
[0090] Conclusion: In comparative example 1, carbon nanotubes are used instead of carbon nanotubes A without surface treatment, and the number of high and low temperature cycles and peel strength are significantly reduced; in comparative example 2, the amount of modified carbon nanotubes added is increased, but the performance is reduced, which shows the importance of controlling the amount added; in comparative example 3, carbon nanotubes are used instead of modified carbon nanotubes C, that is, cuprous oxide is not plated, and the peel strength is significantly reduced; in comparative example 4, chromium and nickel are not plated, and the number of high and low temperature cycles and peel strength are significantly reduced; in summary, the ceramic copper clad laminate prepared by the present invention has good reliability, good durability and high peel strength.
[0091] Finally, it should be noted that the above is only a preferred embodiment of the present invention, but the protection scope of this application is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the spirit and principle of the present invention and within the technical scope disclosed in this application should be included in the protection scope of this application; in the absence of conflict, the embodiments of this application and the features in the embodiments can be combined with each other. Therefore, the protection scope of this application shall be based on the protection scope of the claims.
Claims
1. A processing technology for a ceramic copper-clad laminate, characterized in that: The following steps are involved: S1: Take carbon nanotubes, DMF, and trimethylolpropane triglycidyl ether, heat to 130-140°C and stir for 4-6 hours, add di(2-hydroxyethyl)iminotri(hydroxymethyl)methane and 2,4,6-triaminopyrimidine, keep stirring at 130-140°C for 6-8 hours, filter, dry, and wash to obtain carbon nanotube A; plate chromium and nickel to obtain carbon nanotube B; plate molybdenum and tungsten to obtain carbon nanotube C; plate cuprous oxide to obtain modified carbon nanotubes; S2: mixing the modified carbon nanotubes with copper powder, sintering to obtain a blank; extruding, hot rolling, and cold rolling the blank in sequence to obtain a copper plate; S3: pre-treating the copper plate to obtain a pre-treated copper sheet; The pretreated copper sheet and the aluminum nitride ceramic substrate are brazed with active metal and vacuum sintered to obtain a ceramic copper-clad laminate.
2. The processing technology of a ceramic copper clad laminate according to claim 1, characterized in that: The added amounts of the modified carbon nanotubes and copper powder are as follows: 6-10% of the modified carbon nanotubes and the remainder of the copper powder.
3. The processing technology of a ceramic copper clad laminate according to claim 1, characterized in that: The carbon nanotube A comprises the following raw materials, calculated by mass: 15 to 20 parts of carbon nanotubes, 150 to 200 parts of DMF, 4 to 8 parts of trimethylolpropane triglycidyl ether, 6 to 10 parts of di(2-hydroxyethyl)iminotri(hydroxymethyl)methane, and 10 to 15 parts of 2,4,6-triaminopyrimidine; the carbon nanotube is a hydroxylated single-walled carbon nanotube.
4. The processing technology of a ceramic copper clad laminate according to claim 1, characterized in that: The preparation of the carbon nanotubes B specifically includes the following steps: pre-treating the carbon nanotubes A, plating chromium and nickel on the surface by chemical plating, washing, and drying to obtain the carbon nanotubes B; the chemical plating process specifically includes: placing the pre-treated carbon nanotubes A in a chemical plating solution A with a pH value of 11 to 12 for 50 to 60 minutes at a temperature of 75 to 80° C. The raw materials of the chemical plating solution A are measured in terms of concentration: 6 to 10 g / L of chromium sulfate, 6 to 10 g / L of nickel sulfate, 20 to 25 g / L of disodium ethylenediaminetetraacetate, 10 to 15 g / L of potassium sodium tartrate, and 15 to 20 ml / L of hydrazine hydrate.
5. The processing technology of a ceramic copper clad laminate according to claim 4, characterized in that: The pretreatment specifically includes the following steps: sensitization for 25 to 30 minutes, activation for 10 to 12 minutes; the raw materials of the sensitizing solution are calculated by concentration: 15 to 20 g / L stannous chloride, 60 to 70 ml / L hydrochloric acid, and the rest is water; the raw materials of the activating solution are calculated by concentration: 0.05 to 0.08 g / L palladium chloride, 8 to 9 ml / L hydrochloric acid, and the rest is water.
6. The processing technology of a ceramic copper clad laminate according to claim 1, characterized in that: The preparation of the carbon nanotube C specifically includes the following steps: taking carbon nanotube B, plating molybdenum and tungsten on the surface by chemical plating, washing, and drying to obtain carbon nanotube C; the chemical plating process specifically includes: placing carbon nanotube B in a chemical plating solution B with a pH value of 11 to 12 for 50 to 60 minutes at a temperature of 75 to 80° C. The raw materials of the chemical plating solution B are measured in terms of concentration: 15 to 20 g / L of sodium tungstate, 6 to 10 g / L of molybdenum sulfate, 20 to 25 g / L of disodium ethylenediaminetetraacetate, 10 to 15 g / L of potassium sodium tartrate, and 15 to 20 ml / L of hydrazine hydrate.
7. The processing technology of a ceramic copper clad laminate according to claim 1, characterized in that: The preparation of the modified carbon nanotubes specifically includes the following steps: taking carbon nanotubes C, coating the surface with cuprous oxide by chemical plating, washing, and drying to obtain modified carbon nanotubes; the chemical plating process specifically includes: placing the carbon nanotubes C in a chemical plating solution C for 50 to 60 minutes at a temperature of 75 to 80° C. The preparation of the chemical plating solution C includes the following steps: taking 15 to 20 parts of copper sulfate pentahydrate, 45 to 50 parts of lactic acid, 5 to 8 parts of disodium ethylenediaminetetraacetate, and 1 to 2 parts of formaldehyde, stirring evenly, adding water to dilute to 1 L, and adding sodium hydroxide to adjust the pH to 11 to 12 to obtain the chemical plating solution C.
8. The processing technology of a ceramic copper clad laminate according to claim 1, characterized in that: The steps of copper plate pretreatment are: placing the copper plate in acetone for ultrasonic cleaning, blowing dry, placing it in a chain furnace, introducing nitrogen as a protective gas, introducing oxygen, and treating it at 750-800° C. for 20-25 minutes; wherein the oxygen concentration in the chain furnace is 300 ppm; using a 5wt% sulfuric acid aqueous solution for pickling for 8-10 seconds, washing with water, and drying to obtain a pretreated copper sheet.
9. The processing technology of a ceramic copper clad laminate according to claim 1, characterized in that: The vacuum sintering process is: keeping the temperature at 850-950° C. for 0.5-1 h.
Citation Information
Patent Citations
Preparation method of composite metal layer plated carbon nanotube / graphene composite material
CN109666915A
DBC ceramic substrate with stress relaxation, thermoelectric device and preparation method thereof
CN112713121A